2008
DOI: 10.1002/mame.200800087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Fiber Size on the Physicochemical and Mechanical Properties of Composites of Epoxy and Date Palm Tree Fibers

Abstract: Lignocellulosic fibers from date palm trees were employed to reinforce an epoxy matrix. Two fiber sizes were used, with the length and diameter in the range of 20–30 and 1.5–3 mm, respectively, for the so‐called long fibers, and in the range of 5–15 and 0.25–0.75 mm, respectively, for the so‐called short fibers. The morphologies of the resulting composites, as well as their thermal, mechanical, and water sorption properties were evaluated. Strong interactions between both components and etherification reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…The current study is in keeping with the general pattern aiming at the valorization of lignocellulosics from rejected palms of the date palm tree [19][20][21][22]. Recent papers reported the extraction of nanofibrillated celluloses (NFCs) and cellulose nanocrystals (CNCs) from the leaflets and rachis (axis that bears the leaflets) of palm tree [23,24].…”
Section: Introductionsupporting
confidence: 55%
“…The current study is in keeping with the general pattern aiming at the valorization of lignocellulosics from rejected palms of the date palm tree [19][20][21][22]. Recent papers reported the extraction of nanofibrillated celluloses (NFCs) and cellulose nanocrystals (CNCs) from the leaflets and rachis (axis that bears the leaflets) of palm tree [23,24].…”
Section: Introductionsupporting
confidence: 55%
“…Long and short date palm tree fibres were combined with an epoxy matrix to produce composite materials [22] . The long fibres have a length and diameter of around 25 mm and 2 mm, respectively, whereas the short one possessed a length and diameter of around 10 and 0.5 mm, respectively.…”
Section: Hdsmentioning
confidence: 99%
“…Sbiai et al observed similar trends in the mechanical properties of epoxy composites prepared by reinforcing date palm tree fibers of short and long dimensions [25]. Yemele et al reported similar trends in tensile and flexural properties when high density polythene was reinforced with bark fiber of short, long and particle dimensions with 50% and 60% by weight loading [26].…”
Section: Compressive Strengthmentioning
confidence: 68%